Catalyst-free synthesis of fused Triazolo-Diazepino[5,6-b]Quinoline derivatives via a sequential Ugi-4CR-nucleophilic substitution-intramolecular click reaction - Balalaie, Saeed; Rominger, Frank (Synlett, 2018)
A convenient, post-transformational reaction has been developed for the construction of highly diversified quinoline-fused triazolo-diazepinones featuring four diversification points by employing a catalyst-free Ugi four-component-nucleophilic substitution-intramolecular click cycloaddition sequence. This approach provides a wide scope of products with good yields and high bond-forming efficiency.
Gesehen am 03.03.2020
Der Buchstabe "b" ist im Titel kursiv geschrieben